2006
DOI: 10.1080/01443610600955792
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion and caesarean section in a developing country

Abstract: Our objective was to review blood transfusion practices during caesarean section in a developing country. An audit of 463 consecutive caesarean sections and blood transfusions over a 3-year period (2000 - 2002) was undertaken. The data were collected from the records department in a pre-designed proforma and analysed, using EPI - info Statistical Software version 6. A total of 117 out of 463 (25.2%) caesarean section cases were transfused. The rate of blood transfusion for the various indications were as follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 9 publications
3
29
2
Order By: Relevance
“…They concluded that, in the absence of significant risk factors, routine blood typing and screening at admission for caesarean section did not enhance patient care and should be eliminated. Increased blood loss and transfusion risk in cases of anaemia was reported in other studies 15,16 . The role of anaemia as represented by pre-operative haemoglobin level was also found to be not significantly associated with increased blood loss risk in this study (P >0.05).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…They concluded that, in the absence of significant risk factors, routine blood typing and screening at admission for caesarean section did not enhance patient care and should be eliminated. Increased blood loss and transfusion risk in cases of anaemia was reported in other studies 15,16 . The role of anaemia as represented by pre-operative haemoglobin level was also found to be not significantly associated with increased blood loss risk in this study (P >0.05).…”
Section: Discussionsupporting
confidence: 66%
“…Preeclampsia/-eclampsia 15,16 and acute fatty liver of pregnancy 17 were associated with higher incidence of blood loss and increased risk of blood transfusion. Hypertensive disorders are common and form one of the deadly triad along with hemorrhage and infection that results in much of the maternal morbidity and mortality related to pregnancy 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall blood transfusion incidence is lower in planned surgery (1.58) as compared to emergency surgery (3.58) and unforeseen emergencies occurring during normal delivery (2.82). A Nigerian study 13 had indicated a very high incidence of transfusion (25%), which was probably related to preoperative anemia. The mode of delivery has some influence on blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Nigeria reported that the necessity of transfusion was felt in 59.1 % cases of placenta previa. 9 Rumina T et al 10 studied the need for blood transfusion in 77 subjects with placenta previa in a teaching hospital in Karachi, Pakistan. A total of 177 (mean 2.3) transfusions were received by 59 (76.6%) patients.…”
Section: Resultsmentioning
confidence: 99%